Big Money Thinks Small : Biases, Blind Spots, and Smarter Investing - Tillinghast, Joel (Columbia Business School Publishing, 2017)
Investors are tempted daily by misleading or incomplete information. They may make a lucky bet, realize a sizable profit, and find themselves full of confidence. Their next high-stakes gamble might backfire, not only hitting them in the balance sheet but also taking a mental and emotional toll. Even veteran investors can be caught off guard: a news item may suddenly cause havoc for an industry they've invested in; crowd mentality among fellow investors may skew the market; a CEO may turn out to be unprepared to effectively guide a company. How can one stay focused in such a volatile profession? If you can't trust your past successes to plan and predict, how can you avoid risky situations in the future?In Big Money Thinks Small, veteran fund manager Joel Tillinghast shows investors how to avoid making these mistakes. He offers a set of simple but crucial steps to successful investing, including:· Know yourself, how you arrive at decisions, and how you might be susceptible to self-deception.· Make decisions based on your own expertise, and do not invest in what you don't understand.· Select only trustworthy and capable colleagues and collaborators.· Learn how to identify and avoid investments with inherent flaws.· Always search for bargains, and never forget that the first responsibility of an investor is to identify mispriced stocks. Patience and methodical planning will pay far greater dividends than flashy investments. Tillinghast teaches readers how to learn from their mistakes-and his own, giving investors the tools to ask the right questions in any situation and to think objectively and generatively about portfolio management.